2017
DOI: 10.1111/cei.12929
|View full text |Cite
|
Sign up to set email alerts
|

The influence of macrophages on mesenchymal stromal cell therapy: passive or aggressive agents?

Abstract: SummaryMesenchymal stromal cells (MSC) have emerged as promising cell therapies for multiple conditions based on demonstrations of their potent immunomodulatory and regenerative capacities in models of inflammatory disease. Understanding the effects of MSC on T cells has dominated the majority of work carried out in this field to date; recently, however, a number of studies have shown that the therapeutic effect of MSC requires the presence of macrophages. It is timely to review the mechanisms and manner by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 76 publications
1
63
0
3
Order By: Relevance
“…7a). Without stimulation YMSCs induced more migration in Mφs, while following stimulation AMSCs were more potent in coaxing Mφ migration; these findings were partially consistent with other studies [26, 63, 64]. When RAW264.7 cells following coculture were placed in the inserts (upper compartments) without BMSCs in the plates (lower compartments), coculture with AMSCs resulted in more migratory Mφs compared to coculture with YMSCs, and a significant difference was found following RAW264.7 cell coculture with stimulated YMSCs and stimulated AMSCs (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…7a). Without stimulation YMSCs induced more migration in Mφs, while following stimulation AMSCs were more potent in coaxing Mφ migration; these findings were partially consistent with other studies [26, 63, 64]. When RAW264.7 cells following coculture were placed in the inserts (upper compartments) without BMSCs in the plates (lower compartments), coculture with AMSCs resulted in more migratory Mφs compared to coculture with YMSCs, and a significant difference was found following RAW264.7 cell coculture with stimulated YMSCs and stimulated AMSCs (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…One of the major mechanisms underlying MSC-based therapy is interaction with target cells. MSCs modulate their immunomodulatory effects by suppressing the proliferation and activity of T cells, promoting Treg cells, regulatory DCs and M2 macrophages in a myriad of inflammatory diseases [285]. In case of T cell suppression, Lin et al examined the mRNA expression profiles in mouse T lymphocytes after MSC administration and found that 5 mRNAs including Ccl11, Ccl24, Il13, Il33, and Ear11 were significantly altered [109].…”
Section: The Target Cell Profilementioning
confidence: 99%
“…MSCs have close interplays with macrophages; Proinflammatory M1 macrophages undergo tryptophan depletion upon MSC cytokine mediators via interferongamma (IFN-γ) and prostaglandin E2 secretion and vice versa M1 macrophage recruit MSCs via IFN-γ, monocyte chemoattractant protein 1, and IL-8 30) . Of fi nal note, MSC exosomes have shown to activate VEGF expression via ERK1/2 cascades 31) .…”
Section: Stem Cells Growth Factors and Interleukinsmentioning
confidence: 99%